Preparation and characterization of acid‐treated multiwalled carbon nanotubes interlinked nickel vanadate microcomposites for lithium‐ion batteries. (11th September 2022) - Bandi, Hari; Kakarla, Ashok Kumar; Narsimulu, D.; Shanthappa, R.; Yu, Jae Su
Summary: Vanadium‐based hybrid metal oxides have a crystalline layer structure and excellent kinetics for high‐power‐density lithium (Li)‐ion batteries. Different oxidation levels and harmonizing chemistry of vanadium need a cost‐effective and robust integration approach for the proportion of their form and surface benefits. One of the most attractive methodologies for obtaining pure phase and unique development over varying temperature and pressure conditions is to use hydrothermal technique. Herein, a simple one‐pot hydrothermal procedure is used to make the acid‐treated multiwalled carbon nanotubes (AMWCNTs) decorated on Ni3 V2 O8 (NVO) microspheres (MSs). The synthesized AMWCNTs interlinked NVO (NVO@AMWCNTs) MS composite electrode delievers significantly improved Li‐ion storage capacities when employed as a negative electrode. At 100 mA g −1, the NVO@AMWCNTs MS composite electrode exhibits a specific capacity of 609.6 mA h g −1 as well as excellent cycling stability of 306.6 mA h g −1 at 1000 mA g −1 . The improved electrochemical properties are mainly owing to the large surface area (78.72 m 2  g −1 ), high porosity of connected MSs, and outstanding cooperative chemistry between the NVO and AMWCNTs. The porous structure and high surface area of NVO@AMWCNTs MS composite material allow more voids to adjust the massive amount of Li + ions in the charge‐discharge process. This beneficial composition enhances Li + ion diffusivity and electrical conductivity by increasing the interface area between the electrolyte and electrode, the specific surface area of the electrodes, and the electrolyte absorption.